The Relationship Between Oral Hygiene Knowledge and Oral Hygiene Status of The Elderly In The Periodontia Specialist Poly RSGM UNAIR - Nuril Hanifah; Silvia Prasetyowati; Ratih Larasati; Sri Hidayati (International Journal of Advanced Health Science and Technology, 2025)
The objective this research aimd to ascertain the connection between understanding of oral health and actual mouth cleanliness stats of elderly patients at the Periodontics Specialist Clinic of RSGM Universitas Airlangga. An analytical survey with a cross-sectional method was used for this research. Through purposive sampling, a total of 54 individuals were selected to participate. The findings indicated that most of respondents had a middle level of knowledge regarding oral and dental hygiene, while most exhibited poor oral hygiene status. The Chi-Square test was conducted to the gathered data to examine the correlation between participants’ knowledge and their oral hygiene status. Nevertheless, the analysis revealed no significant association between understanding of oral health and actual mouth cleanliness stats among the elderly. This outcome is presumed to be due to the absence of behavioral data related to the respondents' oral hygiene practices. Consequently, it’s recommended that healthcare providers consistently offer education and counseling on oral and dental care to the elderly in order to enhance their oral health status.